Faktor-Faktor Konflik Di Republik Yaman Berdasarkan Perspektif Abdul Hadi Awang Dan Kesannya Kepada Keadilan Sosial: Factors of Conflict in The Republic of Yemen Based on Abdul Hadi Awang’s Perspective and Its Impact on Social Justice - Abdul Hamid, Muhammad Afifi; Abdul Rahman, Mohamad Zaidi; Raja Sulong, Raja Hisyamuddin (Online Journal of Research in Islamic Studies, 2022)
Yemen has historically been plagued by war and internal upheaval, which has contributed to the geopolitical instability of the republic. The unrest that started 59 years ago has continued in Yemen until the current conflict. The unrest in this republic is brought on by a number of factors. These factors will be detemined and examined based on the perspective of the Honorable (YB) Tan Sri Dato Seri Haji Abdul Hadi bin Awang, Member of Parliament for Marang, Terengganu. Abdul Hadi Awang once went to Yemen in 2010 with a delegation from the Islamic Party of Malaysia (PAS) In order to offer a resolution to the crisis in this nation. Data collection and data analysis are the two main methods that were used. In this study, documentation approaches were used to obtain any relevant data. The thematic analysis and content analysis was utilised to analyse the data. The study’s conclusions, in light of other researchers’ work and the data provided, show that the causes of violence in the Republic of Yemen, as seen from Abdul Hadi Awang’s perspective, are substantial. The power rivalry between Saudi Arabia and the Islamic Republic of Iran as well as the country’s weak government are two factors that contribute to instability in the Republic of Yemen.